Defying Thermodynamics: Stabilization of Alane Within Covalent Triazine Frameworks for Reversible Hydrogen Storage. (5th October 2021) - Stavila, Vitalie; Li, Sichi; Dun, Chaochao; Marple, Maxwell A. T.; Mason, Harris E.; Snider, Jonathan L.; Reynolds, Joseph E.; El Gabaly, Farid; Sugar, Joshua D.; Spataru, Catalin D.; Zhou, Xiaowang; Dizdar, Brennan; et al.
Abstract: The highly unfavorable thermodynamics of direct aluminum hydrogenation can be overcome by stabilizing alane within a nanoporous bipyridine‐functionalized covalent triazine framework (AlH3 @CTF‐bipyridine). This material and the counterpart AlH3 @CTF‐biphenyl rapidly desorb H2 between 95 and 154 °C, with desorption complete at 250 °C. Sieverts measurements, 27 Al MAS NMR and 27 Al 1 H REDOR experiments, and computational spectroscopy reveal that AlH3 @CTF‐bipyridine dehydrogenation is reversible at 60 °C under 700 bar hydrogen, >10 times lower pressure than that required to hydrogenate bulk aluminum. DFT calculations and EPR measurements support an unconventional mechanism whereby strong AlH3 binding to bipyridine results in single‐electron transfer to form AlH2 (AlH3 ) n clusters. The resulting size‐dependent charge redistribution alters the dehydrogenation/rehydrogenation thermochemistry, suggesting a novel strategy to enable reversibility in high‐capacity metal hydrides. Abstract : Experiments and calculations are presented to elucidate the mechanism of nanoconfinement and thermodynamic stabilization of AlH3 inside the pores of a bipyridine‐functionalized cyclic triazine framework, CTF‐bipyridine, which is responsible for the unprecedented reversibility of the hydride under 70 MPa hydrogen pressure at 60 °C.